035 Interferon beta induced thrombotic microangiopathy in multiple sclerosis: a clinical-pathological report. Issue 6 (24th May 2018) - Yam, Charmaine; Fok, Anthony; McLean, Catriona; Butler, Ernest; Kempster, Peter
Abstract : Introduction: Thrombotic microangiopathy (TMA) has been described with long-term interferon-beta (IFN-β). We report a case of biopsy-proven TMA in a patient with multiple sclerosis (MS) who had been having IFN-β−1a injections for twenty years. These biopsy findings were similar to previously described lung histological changes in IFN β- induced pulmonary arterial hypertension (PAH). Case: A 57 year old woman with relapsing-remitting multiple sclerosis had been administering IFN-β−1a injections for twenty years. Her BMI was 21 and she was on a dose of 44 mcg three times per week. She presented with acute pulmonary oedema, renal failure, malignant hypertension, micro-angiopathic haemolytic anaemia and thrombocytopenia after one week of increasing dyspnoea. A renal biopsy showed malignant hypertensive nephropathy and microangiopathy consistent with TMA. Alternative TMA syndromes including haemolytic uraemic syndrome and thrombotic thrombocytopenic purpura were excluded. Renal function stabilised after the IFN was ceased but never returned to the baseline level. Results: Her renal biopsy showed glomerular capillary thrombus deposition, endothelial reactivity, vessel necrosis and wall duplication with luminal thrombus. Fibromuscular proliferation, focal fibrinoid necrosis and luminal thrombus was also present within arterioles. These microvascular histopathological findings resemble vessel changes observed seen in lung biopsies in human IFN β mediated PAH, and those described in transgenic mouse models engineered to overproduce Type 1 IFN. 1 2 Our patient was on treatment for twenty years at a dose exceeding 50 mcg per week. Both are postulated risk factors for the development of TMA. 2 Conclusion: Our report highlights similarities between microvascular changes seen in IFN-induced TMA and those observed in pulmonary arterial hypertension associated with IFN therapy. This suggests a shared pathophysiological mechanism. Kavanagh et al had described a dose-dependent spectrum of renal microvascular disease in his mouse model. 2 The duration and high dosage for weight of IFN Β supports a cumulative drug toxicity effect. References: . Fok A, Williams T, McLean C, Butler E. Interferon beta- 1a long-term therapy related to pulmonary arterial hypertension in multiple sclerosis patients. Mult Scler2016Oct;22(11):1495–1498. . Kavanagh D, McGlasson S, Jury A, et al. Type I interferon causes thrombotic microangiopathy by a dose-dependent toxic effect on the microvasculature. Blood2016Aug;05–715987.